Mixed dyslipidemia and the evolution risk of cardiovascular diseases in elders (Research, Society and Development, 2021)
Dyslipidemia causes changes in serum lipid levels (increases plasma triglycerides, LDL, and cholesterol or decreases HDL levels), which is one of the factors responsible for increased cardiovascular risk. In this sense, the present review aimed to assess the relationship between the occurrence of mixed dyslipidemia and the evolution risk of cardiovascular disease in elders, as well as its main behavioral causes. The bibliographic search was made on scientific bases such as SciELO, PubMed, Google Scholar and Lilacs. From the total papers (585,558 papers), twenty-three were selected to compose this literature review. It has been observed that mixed dyslipidemia increases the likelihood of cardiovascular effects in elder, i.e., there is a straight relationship between these two factors, which are mainly caused by unhealthy habits, such as obesity, sedentary lifestyle, unhealthy diet, smoking, and consumption of alcoholic beverages. In addition, the disease is mainly associated with feminine gender.